A Novel Enzymatic Strategy for the Synthesis of Substituted Tetrahydroisoquinolines. Issue 8 (6th June 2016) - Bonamore, Alessandra; Calisti, Lorenzo; Calcaterra, Andrea; Ismail, Omar H.; Gargano, Maurizio; D'Acquarica, Ilaria; Botta, Bruno; Boffi, Alberto; Macone, Alberto
Abstract: A fully enzymatic asymmetric synthesis of substituted tetrahydroisoquinolines was achieved in two steps starting from dopamine and a set of amine substrates by coupling the activity of a plant diamine oxidase with the recombinant norcoclaurine synthase enzyme from Thalictrum flavum . In the first step, a variety of aliphatic and aromatic amines of general interest as pharmaceutical building blocks were transformed into the corresponding aldehydes by the broad specificity of diamine oxidase enzyme from Lathyrus cicera . In the second step, the stereoselectivity of the norcoclaurine synthase catalyzed reaction to yield (S)‐configured tetrahydroisoquinoline products was exploited by mixing the aldehyde obtained in the first step with dopamine, the committed substrate for the Pictet‐Spengler reaction. The reactions were carried out in aqueous buffer and the products thus obtained were extracted and characterized by chiral GC/MS. Enantiomeric excess > 99% were obtained for all substrates investigated. The method provided a set of novel tetrahydroisoquinolines with potentially interesting pharmacological profiles. Abstract : A fully enzymatic asymmetric synthesis of substituted tetrahydroisoquinolines is achieved in two steps starting from dopamine and a set of amine substrates by coupling the activity of Lathyrus cicera diamine oxidase with the recombinant norcoclaurine synthase from Thalictrum flavum .